2015
DOI: 10.4103/1596-3519.149878
|View full text |Cite
|
Sign up to set email alerts
|

A 3 year audit of adult epilepsy care in a Nigerian tertiary hospital (2011-2013)

Abstract: Less than half of our patients had good epilepsy control. To improve on drug compliance attending physicians need to prescribe more of the relatively cheaper AED like the phenobarbitone and to optimize drug dosage before switching to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[3235] In Nigeria, the prevalence of nonadherence was found to be 21% and in Uganda it was 46%. [3440] The percentage was higher in a study which looked into the mortality of epilepsy among patients in an endemic area with onchocerciasis in Uganda (64%). [41] These differences in the level of adherence might be attributed to social, environmental, and racial differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3235] In Nigeria, the prevalence of nonadherence was found to be 21% and in Uganda it was 46%. [3440] The percentage was higher in a study which looked into the mortality of epilepsy among patients in an endemic area with onchocerciasis in Uganda (64%). [41] These differences in the level of adherence might be attributed to social, environmental, and racial differences.…”
Section: Discussionmentioning
confidence: 99%
“…[29] In Nigeria, Sanya et al showed that 21 (21%) did not comply with the use of given AED. [34] While in a primary care study in the UK showed that 36% of the patients were nonadherent. A total of 15% had low necessity scores, while 36% had strong concerns about AEDs, i.e.…”
Section: Introductionmentioning
confidence: 99%